Design of proteins with photocontrollable structure and function and their applications - Janković, Brankica (Biologia Serbica, 2022)
Nature employs very sophisticated strategies of using light to control certain biological processes such as vision or photosynthesis. If we borrow that concept from Nature and make it universally applicable to a wide variety of proteins, we would be able to control many aspects of life on a molecular level. One of the goals is to design proteins to be specifically photo-responsive, so that light can be used to trigger the conformational changes which are subsequently followed by real-time spectroscopy. Such a combination of tools enabled the studies of interesting biochemical phenomena such as protein binding mechanisms and allostery. More precisely, the design of a protein-peptide interaction that can be light-controlled, enabled the detailed kinetics investigation of their binding mechanisms. Furthermore, the design of a photoswitchable allosteric proteins made it possible to directly investigate the speed of allosteric signaling within the single domains. Many other proof-of-concept studies and possible applications of photocontrollable proteins will be discussed.